Posterior hypothalamic modulation of ocular‐responsive trigeminal subnucleus caudalis neurons is mediated by Orexin‐A and Orexin1 receptors. (6th June 2014) - Katagiri, Ayano; Okamoto, Keiichiro; Thompson, Randall; Rahman, Mostafeezur; Bereiter, David A.
Abstract Orexin‐A (OxA) is synthesized in posterior and lateral regions of the hypothalamus and contributes to homeostatic regulation of body functions including pain modulation. To determine if orexinergic mechanisms contribute to posterior hypothalamus (PH)‐induced modulation of ocular input to subnucleus caudalis/upper cervical (Vc/C1) neurons, the orexin‐1 receptor antagonist SB334867 was applied to the dorsal brainstem surface prior to PH disinhibition, by bicuculline methiodide, in male rats under isoflurane anesthesia. Ocular input to Vc/C1 units by bright light or hypertonic saline was markedly reduced by PH disinhibition and reversed completely by local Vc/C1 application of SB334867. OxA applied to the Vc/C1 surface mimicked the effects of PH disinhibition in a dose‐dependent manner. OxA‐induced inhibition was prevented by co‐application of SB334867, but not by the orexin‐2 receptor antagonist TCS Ox2 29. PH disinhibition and local OxA application also reduced the high threshold convergent cutaneous receptive field area of ocular units, suggesting widespread effects on somatic input to Vc/C1 ocular units. Vc/C1 application of OxA or SB334867 alone did not affect the background discharge of ocular units and suggested that the PH–OxA influence on ocular unit activity was not tonically active. Vc/C1 application of OxA or SB334867 alone also did not alter mean arterial pressure, whereas PH disinhibition evoked prompt and sustained increases. These results suggest that stimulus‐evoked increases in PH outflow acts through OxA and orexin‐1 receptors to alter the encoding properties of trigeminal brainstem neurons responsive to input from the ocular surface and deep tissues of the eye.